Surface morphology and particle size analysis of Ba(0.5)Sr(0.5)TiO(3) nano-powder grown using sol-gel method - R., Balachandran; H. K., Yow; B. H., Ong; K., Anuar; W. T., Teoh; K. B., Tan (2008)
Barium Strontium Titanate powder in the form of nano cubic particles has been prepared using slow rate gellification by sol-gel method. X-Ray Diffractometer results show that single phase formation occurred at 800 degrees C and the crystallite size for this sample was found to be 36.06 mn. Scanning Electron Microscopy analysis shows that the particles in the sample calcinated at 800 degrees C do not agglomerate and the average particle size was found to be 42.30 nm. The nano particle size analyzer results show a narrow particle distribution with good uniformity.